Alpha-Numerals Recognition: Vehicle Number Plate Recognition (VNPR) - Rajput, Hitesh (IIT (BHU), Varanasi, 2014)
Now a days vehicle play a vital role in transportation. Also the use of vehicles has been increasing because of population growth and human needs in recent years. Therefore, control of vehicles is becoming a big problem in every country and is much more difficult to solve. Sometimes it becomes difficult to identify vehicle owner who violates traffic rules and drives too fast. Therefore, it is not possible to catch and punish those kinds of people because the traffic personal might not be able to retrieve vehicle number from the moving vehicle because of the speed of the vehicle. Therefore, there is a need to develop Vehicle Number Plate Recognition system (VNPR) to deal with this problem. There are numerous VNPR systems available today. These systems are utilized frequently for access control in buildings and parking areas, law enforcement, stolen car detection, traffic control, automatic toll collection and marketing research. These systems are based on different methodologies but still perfect recognition remains a challenging task because some of the factors like high speed of vehicles, non-uniform vehicle number plates, language of vehicle number and different lighting conditions. Most of the systems work under these limitations
Alpha-Numerals Recognition, VNPR
Keywords: Alpha-Numerals Recognition